Characterization of Fungal Colonization of Indwelling Esophagostomy Tubes - Shelly J. Olin; David A. Bemis; John R. Dunlap; Jacqueline C. Whittemore (Case Reports in Veterinary Medicine)
Fungal colonization of feeding tubes occurs rapidly in people, resulting in decreased structural integrity and complications such as luminal obstruction and tube failure. Esophagostomy tubes (E-tubes) are commonly used in dogs and cats for enteral support, but data are lacking regarding colonizing fungi and the impact of colonization on tube integrity. In this study, esophagostomy tubes were collected in lieu of disposal from dogs and cats undergoing feeding tube exchange. Fungi were isolated with culture and identified using morphological characteristics. Scanning electron microscopy was used to evaluate the surface characteristics of the tubes. Two silicone and one polyurethane E-tube were evaluated. Fungi associated with the normal microbiota, including Candida sp. and Penicillium sp., as well as environmental fungi were identified. This case series represents the first documentation of fungal colonization of silicone and polyurethane E-tubes in dogs and cats. Additionally, this is the first report to document degenerative changes in a silicone E-tube.